2018
DOI: 10.1016/j.antiviral.2018.06.015
|View full text |Cite
|
Sign up to set email alerts
|

TLR7 polymorphism, sex and chronic HBV infection influence plasmacytoid DC maturation by TLR7 ligands

Abstract: A B S T R A C TTLR7 agonists are of high interest for the treatment of cancer, auto-immunity and chronic viral infections. They are known to activate plasmacytoid dendritic cells (pDCs) to produce high amounts of Type I Interferon (IFN) and to facilitate T and B cell responses, the latter with the help of maturation markers such as CD40, CD80 and CD86. The TLR7 single nucleotide polymorphism (SNP) rs179008 (GLn11Leu), sex and chronic viral infection have all been reported to influence pDC IFN production. It is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 50 publications
(71 reference statements)
3
11
0
Order By: Relevance
“…In our study, the prevalence of TLR7 rs179008 AA, AT, and TT genotypes in healthy controls was 81.0%, 16.5%, and 2.5%. This finding was unmatched with that of the other studies carried out by [12,13,29,14]. The occurrence of TLR7 rs179008A/T allelic frequency was comparable with the study carried out by Valverde-Villegas et al, 2017, [30,6,16] and dissimilar with the study reported by [6,12,13,29].…”
Section: Discussionsupporting
confidence: 79%
“…In our study, the prevalence of TLR7 rs179008 AA, AT, and TT genotypes in healthy controls was 81.0%, 16.5%, and 2.5%. This finding was unmatched with that of the other studies carried out by [12,13,29,14]. The occurrence of TLR7 rs179008A/T allelic frequency was comparable with the study carried out by Valverde-Villegas et al, 2017, [30,6,16] and dissimilar with the study reported by [6,12,13,29].…”
Section: Discussionsupporting
confidence: 79%
“…We also report an association between CMV DNA status and rs179008, a non-synonymous A > T (Gln11Leu) polymorphism within exon 3 of the TLR7 gene [43]. The resulting glycine to leucine change has been suggested to code for a functionally impaired TLR7 protein [44,45]. In the present study, the T allele was associated with significantly lower odds of CMV positivity.…”
Section: Discussionsupporting
confidence: 58%
“…It is suggested that estrogen has a suppressive effect on HCC because it is known that the prevalence of HCC is high in males, and low in premenopausal females [37]. It is also implied that there are sex differences in response to HBV infection [38]. It was demonstrated that URI1 inhibits NAD synthesis by suppressing the function of estrogen receptor in hepatocytes, leading to the development of HCC [10].…”
Section: Discussionmentioning
confidence: 99%